Impact of Leadership Styles on Organizational Productivity: a Case Study Of Zenith Bank Nigeria PLC - Kehinde, Segun (MultiTech Publisher, 2024)
This study investigates the profound influence of leadership styles on organizational productivity, focusing on a case study of Zenith Bank Nigeria Plc within the banking industry. Leadership plays a pivotal role in shaping the culture and efficiency of an organization, and this research examines the specific leadership styles and their effects on employee performance, teamwork, and overall productivity. By analyzing the dynamic relationship between leadership and productivity, this study aims to provide valuable insights for both the banking industry and leadership development. It explores the challenges and opportunities within Zenith Bank Nigeria Plc and suggests strategies for optimizing leadership approaches to enhance organizational performance. The findings of this research have practical implications for leaders, managers, and stakeholders in the banking sector, offering a deeper understanding of how leadership styles can be harnessed to drive increased productivity and competitiveness. This study contributes to the ongoing discourse on effective leadership within the banking industry, facilitating informed decision-making and promoting sustained growth and success.